Neighbourhood Supports for Active Ageing in Urban India. (September 2020) - Adlakha, Deepti; Krishna, Murali; Woolrych, Ryan; Ellis, Geraint
Developing urban environments that promote healthy, active living for older adults is at the forefront of global planning policy debates, resulting in concepts and design guidelines to support population ageing. However, current urban planning in India is overlooking the design of age-friendly cities. The share of older adults in India is estimated to increase from 8 per cent in 2015 to 20 per cent in 2050. This demographic shift towards a higher proportion of older adults and the associated health and social care expenditures make healthy ageing a public health priority. Existing studies in gerontology have focused on improving housing environments, but we are now understanding the significance of neighbourhood environments for active ageing. This study contributes to the knowledge on factors shaping active ageing in urban India. We present findings from 55 semi-structured interviews conducted with older adults (age > 60 years) in the metropolitan cities of New Delhi and Chennai in India. The findings explore three themes that emerged from this research: (a) neighbourhood design for active ageing, (b) social participation in community spaces and (c) navigating urban transport and mobility. Across these themes, this study highlights that access to neighbourhood amenities such as transportation, parks and green spaces, and opportunities for leisure and social interaction play a key role in determining older adults' health and quality of life. In drawing on older adults' lived experiences in their communities, this study informs policy efforts to improve neighbourhood supports for active ageing in urban India.